p53/sirtuin 1/NF-κB Signaling Axis in Chronic Inflammation and Maladaptive Kidney Repair After Cisplatin Nephrotoxicity - Fu, Ying; Wang, Ying; Liu, Yuxue; Tang, Chengyuan; Cai, Juan; Chen, Guochun; Dong, Zheng (Frontiers in Immunology, 2022)
Chronic inflammation contributes to maladaptive kidney repair, but its regulation is unclear. Here, we report that sirtuin 1 (SIRT1) is downregulated after repeated low-dose cisplatin (RLDC) injury, and this downregulation leads to p65 acetylation and consequent NF-κB activation resulting in a persistent inflammatory response. RLDC induced the down-regulation of SIRT1 and activation of NF-κB, which were accompanied by chronic tubular damage, tubulointerstitial inflammation, and fibrosis in mice. Inhibition of NF-κB suppressed the production of pro-inflammatory cytokines and fibrotic phenotypes in RLDC-treated renal tubular cells. SIRT1 activation by its agonists markedly reduced the acetylation of p65 (a key component of NF-κB), resulting in the attenuation of the inflammatory and fibrotic responses. Conversely, knockdown of SIRT1 exacerbated these cellular changes. At the upstream, p53 was activated after RLDC treatment to repress SIRT1, resulting in p65 acetylation, NF-κB activation and transcription of inflammatory cytokines. In mice, SIRT1 agonists attenuated RLDC-induced chronic inflammation, tissue damage, and renal fibrosis. Together, these results unveil the p53/SIRT1/NF-κB signaling axis in maladaptive kidney repair following RLDC treatment, where p53 represses SIRT1 to increase p65 acetylation for NF-κB activation, leading to chronic renal inflammation.